Volumetric assessment is superior to axial measurements in estimating the outcome of patients with acute uncomplicated type B aortic intramural haematoma. (29th March 2022) - Chen, Min; Yang, Fan; Chen, Lyufan; Liu, Jitao; Luo, Songyuan; Li, Jie; Huang, Wenhui; Liu, Yuan; Fan, Ruixin; Geng, Qingshan; Chen, Jiyan; Luo, Jianfang
Abstract: OBJECTIVES: Our goal was to investigate the accuracy of the two-dimensional and three-dimensional computed tomography imaging features in predicting the progression of acute uncomplicated type B aortic intramural haematoma (IMH). METHODS: This study retrospectively screened 140 patients diagnosed with acute uncomplicated type B IMH in our institution from January 2015 to December 2020. Patients were classified as exhibiting progression (aortic dissection, aortic rupture, aneurysm formation, ulcer-like projection depth >10 mm or >10% increase in the initial thickness of the aortic wall) and regression (completely or partially reabsorbed haematoma) based on follow-up computed tomography. RESULTS: During the 11.4-month follow-up [interquartile range (IQR), 2.6–17.8], 55 patients had haematoma progression. The progression group had higher haematoma volume (HV) and total lesion volume [94.8 (IQR, 80.0–108.2) cm 3 vs 40.3 (IQR, 30.8–57.9) cm 3 ; 278.0 (IQR, 238.6–369.3) cm 3 vs 197.3 (IQR, 152.8–235.9) cm 3, both P < 0.001) and longer lesion length [43.2 (IQR, 37.5–46.7) cm vs 30.4 (IQR, 28.1–37.6) cm, P < 0.001)] than the regression group. According to the area under the curve, HV > 66 cm 3 is the greatest risk factor for haematoma progression. In multivariable analysis, HV was a powerful independent predictive factor for type B IMH progression, with a hazard ratio of 17.9 (95% confidence interval, 5.5–58.7; P < 0.001). CONCLUSIONS: Volumetric parameters may help to predict disease progression more precisely for patients with acute uncomplicated type B IMH compared to standard axial measurements, which might optimize the initial treatment and follow-up protocol. Abstract : Aortic intramural haematoma (IMH) is one of the typical entities of the acute aortic syndrome and probably accounts for 5–25% of all cases [1].